Development of a compression test device for investigating interaction between diffusion of biodiesel and large deformation in rubber - Chai, A.B.; Andriyana, A.; Verron, E.; Johan, M.R.; Haseeb, A.S. Md. Abdul (2011)
Motivated by environmental and economic factors, biodiesel has been introduced to partially replace the diminishing stock of petroleum-based fuel. However, the use of biodiesel such as palm biodiesel is placing additional demands on automotive components, e.g. rubber components, due to a compatibility issue in the fuel system. In engineering applications where hostile environments are involved, the long-term mechanical response of rubber components is affected by interactions existed between diffusion of liquids into the material and fluctuating multiaxial loading. Hence, it is crucial to investigate the durability of rubber components in this aggressive environment. A number of studies on static immersion tests to investigate the diffusion of liquids in stress-free rubber can be found in the literature. However, studies focusing on the coupling between diffusion and large deformation in rubber, and the resulting swelling and mechanical response under cyclic loading conditions are less common. In the present work, a compression device for the investigation of interaction between diffusion of palm biodiesel and large compressive strain in rubber is developed. The apparatus is comprised of four rectangular stainless steel plates with spacer bars in between, which are designed such that pre-compression can be introduced on the rubber specimens while they are immersed into biodiesel. This allows diffusion and large strain to take place simultaneously. Different pre-compressive strains and biodiesel blends are considered. At the end of each immersion period, the resulting swelling behavior and mechanical response of rubber specimens under cyclic loading conditions are investigated. The features of this compression device are discussed and perspectives are drawn. (C) 2011 Elsevier Ltd. All rights reserved.